Molecular genetic analysis of colorectal carcinoma with an aggressive extraintestinal immunohistochemical phenotype - Hrudka, Jan; Kalinová, Markéta; Fišerová, Hana; Jelínková, Karolína; Nikov, Andrej; Waldauf, Petr; Matěj, Radoslav (Scientific reports, 2024)
Colorectal cancer (CRC) is a leading global cause of illness and death. There is a need for identification of better prognostic markers beyond traditional clinical variables like grade and stage. Previous research revealed that abnormal expression of cytokeratin 7 (CK7) and loss of the intestinal-specific Special AT-rich sequence-binding protein 2 (SATB2) are linked to poor CRC prognosis. This study aimed to explore these markers' prognostic significance alongside two extraintestinal mucins (MUC5AC, MUC6), claudin 18, and MUC4 in 285 CRC cases using immunohistochemistry on tissue microarrays (TMAs). CK7 expression and SATB2-loss were associated with MUC5AC, MUC6, and claudin 18 positivity. These findings suggest a distinct "non-intestinal" immunohistochemical profile in CRC, often right-sided, SATB2-low, with atypical expression of CK7 and non-colorectal mucins (MUC5AC, MUC6). Strong MUC4 expression negatively impacted cancer-specific survival (hazard ratio = 2.7, p = 0.044). Genetic analysis via next-generation sequencing (NGS) in CK7 + CRCs and those with high MUC4 expression revealed prevalent mutations in TP53, APC, BRAF, KRAS, PIK3CA, FBXW7, and SMAD4, consistent with known CRC mutation patterns. NGS also identified druggable variants in BRAF, PIK3CA, and KRAS. CK7 + tumors showed intriguingly common (31.6%) BRAF V600E mutations corelating with poor prognosis, compared to the frequency described in the literature and databases. Further research on larger cohorts with a non-colorectal immunophenotype and high MUC4 expression is needed.
Keywords: Colorectal Neoplasms; mužské pohlaví; Male; Mucin-6; senioři; senioři nad 80 let; keratin-7; Proto-Oncogene Proteins B-raf; Immunohistochemistry; NGS; Mucin; protoonkogenní proteiny p21(ras); Humans; fenotyp; Female; protoonkogenní proteiny B-Raf; Prognosis; Keratin-7; Mucin 5AC; Colorectal carcinoma; lidé; transkripční faktory; imunohistochemie; mucin 5AC; Biomarkers, Tumor; Middle Aged; ženské pohlaví; lidé středního věku; nádorové biomarkery; vysoce účinné nukleotidové sekvenování; Matrix Attachment Region Binding Proteins; Phenotype; Class I Phosphatidylinositol 3-Kinases; vazebné proteiny DNA v oblastech připojení k matrix; mucin 6; prognóza; Aged, 80 and over; Transcription Factors; Cytokeratin 7; mutace; Claudin 18; kolorektální nádory; Mucin-4; dospělí; Mutation; Adult; High-Throughput Nucleotide Sequencing; mucin 4; fosfatidylinositol-3-kinasy třídy I; Aged; Proto-Oncogene Proteins p21(ras); SATB2